2012
DOI: 10.1159/000338272
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and Renal Mass Ablation Synergistically Augment Albuminuria in the Diabetic Subtotally Nephrectomized Rat: Implications for Modeling Diabetic Nephropathy

Abstract: Background/Aims: While experimental models that emulate diabetic nephropathy are valuable tools for elucidating pathogenetic mechanisms and developing novel therapies, existing models imperfectly recapitulate human disease. In diabetes, hyperglycemia and hemodynamic forces act in concert to induce renal injury. Accordingly, in the present study, we combined streptozotocin-induced diabetes with surgical ablation of 5/6 of the kidney mass with the aim of evaluating their additive effects on renal function and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
1
0
2
Order By: Relevance
“…Therefore, renal tissue of diabetic animals subjected to nephrectomy demonstrated slight, segmental and focal tubulointerstitial changes. In diabetic nephropathy, cells accumulate glycogen and collagen fibers in the mesangial region and in the basal membrane showing glomerulosclerosis, tubulointerstitial fibrosis, mesangial expansion, deposits of extracellular matrix, and tubulointerstitial changes (28,29). Therefore, this study reproduced the synergism found in the physiopathology of diabetic nephropathy by means of hemodynamic and oxidative mechanisms associated with histological changes.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, renal tissue of diabetic animals subjected to nephrectomy demonstrated slight, segmental and focal tubulointerstitial changes. In diabetic nephropathy, cells accumulate glycogen and collagen fibers in the mesangial region and in the basal membrane showing glomerulosclerosis, tubulointerstitial fibrosis, mesangial expansion, deposits of extracellular matrix, and tubulointerstitial changes (28,29). Therefore, this study reproduced the synergism found in the physiopathology of diabetic nephropathy by means of hemodynamic and oxidative mechanisms associated with histological changes.…”
Section: Discussionsupporting
confidence: 74%
“…Excessive ROS production triggers renal fibrosis and inflammation. 20 27 Hyperglycemia induced ROS formation and activated NF-κB, thus resulting in increased inflammatory cytokine concentrations in the kidneys of diabetic rats. 25 Hyperglycemia-induced increase in ROS formation also activated the TLR4 signaling pathway in the cardiomyopathy of rats with STZ-induced DM.…”
Section: Discussionmentioning
confidence: 99%
“…(67) . Estudos in vivo demonstram que a hipertrofia renal se define como o estágio inicial da ND (68,69) .…”
Section: Teles Et Al (2009) Demonstraram Que O Controle Da Glicemia unclassified
“…O aumento da albuminúria nos animais diabéticos nefrectomizados reforçou a importância da nefrectomia para acelerar a progressão da ND e se confirmou como modelo amplamente utilizado em inúmeros trabalhos experimentais (35,55,68) .…”
Section: Teles Et Al (2009) Demonstraram Que O Controle Da Glicemia unclassified